Understanding students’ abstractions in block-based programming environments: A performance based evaluation - Çakıroğlu, Ünal; Çevik, İsak; Köşeli, Engin; Aydın, Merve (Thinking skills and creativity, 2021)
•The study examined the effect of using block-based coding environments on enhancing secondary school students’ abstraction skills.•A rubric was created to reveal the students’ abstraction performances.•The students performed high in elimination, focusing and generalization; however, students’ performances were relatively low in customization.•The nature of the problems, affordances of block-based programming environments and coding constructs were the factors affected the abstraction process. Providing computational problems for enhancing students’ abstraction skills and monitoring how students make abstractions is difficult in block-based programming environments (BBPEs). Thus, concrete examples and principles are needed to guide computer science teachers about understanding and enhancing students’ abstractions. This study aims to examine the effect of using block-based coding environments on enhancing secondary school students’ abstraction skills. Referring to the programming knowledge, a rubric was created to analyze the data from screen recordings, observation and interviews were used together to reveal the students’ abstraction performances. The results suggested that students performed high in elimination, focusing and generalization; however, students’ performances were relatively low in customization. Students’ explanations were mostly related the nature of the problems, affordances of BBPE and the programming constructs used in coding. We hope the study will provide insights for the efforts on instructional designs for successful abstraction experiences for young students.